[PP.13.02] IMPACT OF STATINS ON THE PERINDOPRIL/AMLODIPINE ANTIHYPERTENSIVE EFFICACY IN PATIENTS WITH HYPERCHOLESTEROLEMIA: SUBANALYSIS OF THE PERSPECTIVA STUDY. (September 2016) - Sirenko, Y.; Radchenko, G.
Abstract : Objective: The majority of patients with frequently coexisted hypertension and hypercholesterolemia require combination treatment with a statins and antihypertensives. To reach the blood pressure (BP) control in these patients is hard, but there is evidence of a synergistic BP-lowering effect of statins added to antihypertensive therapy. The objective of this subanalysis of the PERSPECTIVA study was to assess the impact of statins on antihypertensive efficacy of single-pill combination (SPC) perindopril and amlodipine in hypertensive patients with hypercholesterolemia. Design and method: The PERSPECTIVA study included 701 patients with newly diagnosed hypertension or hypertension uncontrolled on monotherapy or free dual-combination therapy (systolic BP >/ = 140 mmHg and/or diastolic BP >/ = 90 mmHg). Patients were started on SPC perindopril 5 mg/amlodipine 5 mg (if previously untreated), or switched to SPC perindopril 10 mg/amlodipine 5 mg (if systolic BP >/ = 140 and < 180 and/or diastolic BP >/ = 90 and <110 mmHg), or SPC perindopril 10 mg/amlodipine 10 mg (if systolic BP >/ = 180 and <200 and/or diastolic BP >/ = 110 and/or <120 mmHg). We compared the antihypertensive efficacy of SPC in 226 patients wit hstatin therapy at baseline (statin (+) vs 361 patients without statins (statin (-), over a follow-up period of 60 days. Results: At day 60, rate of BP control (<140/90 mmHg) was significantly greater in the statin (+) vs statin () group: 73% vs 64% respectively (+14%, P<0.05). In the statin (+) group, SPC perindopril/amlodipine significantly reduced BP in patients previously untreated, or treated with monotherapy, dual therapy, or triple therapy: -38.8/-20, -39.1/-20.1, -38/-19.4, -39.9/-18.3 mmHg respectively (P < 0.001 vs baseline BP). Treatment was well tolerated with a similar rate of adverse events: 0.9% in the statin (+) vs 2.5% in the statin (-) groups. Conclusions: In hypertensive patients the addition of a statin to perindopril/amlodipine SPC resulted in significantly better BP control and BP reduction regardless of previous antihypertensive therapy. Furthermore, the combination of statin plus perindopril/amlodipine was well tolerated. This subanalysis of the PERSPECTIVA study supports the synergistic effect of statins and perindopril/amlodipine combination.